Development of an eLearning intervention for enhancing health professionals’ skills for addressing COVID-19 vaccine hesitancy - Papadakis, Sophia; Anastasaki, Marilena; Gamaletsou, Maria; Papagiannopoulou, Xenia; Aligizakis, Eftychios; Lionis, Christos (Frontiers in Medicine, 2023)
Like many countries, Greece has faced resistance to coronavirus disease 2019 (COVID-19) vaccination among residents for both the initial and booster doses. Supporting healthcare professionals with delivering brief advice on COVID-19 vaccination may assist with reaching national vaccination targets. We sought to rapidly develop, pilot test, and deploy an eLearning intervention on skills training on effective techniques for addressing COVID-19 vaccine hesitancy for primary health and social care professionals in Greece. A five-part, 1.5-h eLearning was produced in Greek which featured two behavior change techniques, Very Brief Advice (VBA) and Motivational Interviewing (MI) adapted for use in addressing COVID-19 vaccine hesitancy. Six-film-based case studies modeling the use of VBA and MI in the context of challenging scenarios typically seen in Greek health and social settings were produced for the eLearning. The CME was pilot tested using a pre-post design in a small convenience sample (n = 17) of health care professionals. Pilot study results found the training provided new knowledge (80%), improved provider skills (80%), and was useful to provider’s clinical practice (90%). There was a mixed effect in provider capability, motivation, and opportunity. Ninety percent of providers strongly agreed or agreed that they planned to use the information and skills provided by the training in their clinical practice. This project has resulted in new training assets for use by health and social professional tailored to the nationally context in Greece including supporting uptake of booster doses of the COVID-19 vaccine.